Terapeutik face massage-teknik self healing untuk menghadapi tingginya kasus kehamilan berisiko - Indriyani Makmun; Rizkia Amilia; Catur Esty Pamungkas; Ni Wayan Ari Adiputri; Nova Irmayanti; Ayu Andira (Universitas Mataram, 2023)
Anxiety can have a negative impact on both the mother and the development of the fetus. If the mother constantly maintains anxiety can interfere with fetal growth and development, resulting in premature birth or when adults experience learning difficulties, hyperactivity and even autism. The purpose of this community service is to provide Self healing with Therapeutic Face Massage Techniques in dealing with high-risk pregnancy cases. The methods used include providing education and practice directly to the participants and evaluating what the mother felt after the therapy was given. The results of the service activities are evidenced by the activeness of participants in this activity, the implementation of activities has been able to reduce anxiety felt by pregnant women and the Face Massage Technique provided refreshment and a comfortable sense of relaxation in pregnancy. The results of this activity have been able to play an active role of patients in the process of relaxing the mother's psychological condition with Therapeutic Face Massage - Self Healing Techniques so that the level of anxiety felt by the mother is reduced and the pregnancy is always healthy and fit.